Rescue Revolution: Cutting-Edge Practices in Disaster Response - Mohd Perdaus, Ahmad Faizal bin; Kharie, Mohamad Fadli bin; Hasan, Fauziah Mohd (International Journal of Human and Health Sciences (IJHHS), 2025)
Geographic Information Systems (GIS) are essential tools in disaster management, providing critical spatial analysis and visualization capabilities. This presentation explores the diverse applications of GIS throughout various stages of disaster management, including risk assessment, monitoring, and resource allocation. By integrating multiple data sources, such as satellite imagery and sensors, GIS allows authorities to identify highrisk zones, strategize disaster responses, and optimize the distribution of relief resources. Furthermore, GIS plays a vital role in public health responses by facilitating both offline and online surveys to track disease outbreaks and ensure efficient healthcare resource allocation. It also fosters community engagement by delivering real-time risk updates and enabling two-way communication between citizens and emergency services. Ultimately, this presentation highlights the transformative impact of GIS on enhancing the efficiency and coordination of disaster management efforts. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S15